Penyuluhan Pemantauan Status Gizi Balita di Desa Kedungsoka Kecamatan Puloampel Kabupaten Serang Provinsi Banten - Novrita Tri Yulvia; Defi Selfianita; Teresha Gamaliel Panjaitan; Reza Novanty; Liawati Liawati (Pusat Riset dan Inovasi Nasional, 2024)
Good nutritional status of toddlers plays an important role in growth and development, especially in the golden period in the first five years. The purpose of this activity is to increase mothers' knowledge of the nutritional status of toddlers so that it can reduce the incidence of malnutrition or undernutrition in toddlers. This community service activity was carried out in Kp. Kali Keranjang, Kedungsoka Village, Puloampel District, Serang Regency by weighing toddlers, providing counseling to parents/caregivers of toddlers, This community service activity was attended by 30-35 toddlers. Through education about balanced nutrition, there has been an increase in mothers' knowledge about balanced nutrition in toddlers. Increased knowledge about balanced nutrition and food selection may be followed by changes in behavior. Nutrition counseling with the lecture method and ongoing nutritional status examinations are one of the learning approaches by providing a set of knowledge and skills needed to be able to determine the right behavioral choices to improve the nutritional status of their toddlers.